Affectation of the first permanent molar and effect of an educational strategy in an educational institution in the city of Medellin: 2016-2019 - Franco-Aguirre, John Querubín; Díaz-Garavito, María Victoria (Revista Facultad de Odontología Universidad de Antioquia, 2021)
Introduction: the lack of knowledge about the importance of the first permanent molar in oral health continues to be a problem in a large part of the population. The objectivewas to evaluate the effectiveness of an educational strategy for the preservation of the permanent first molar (PMP) in school children of an educational institution in Medellin. Methods: follow-up study of an educational intervention between 2016 and 2019 in a sample of 35 schoolchildren between 12 and 13 years of age, who were screened for modified CPO-D and plaque index according to Silness & Loe. Thirty-five parents were surveyed about knowledge and practices in oral health and the permanent first molar, and educational activities with emphasis on the care of the first molar were carried out for schoolchildren. The data were analyzed through descriptive and bivariate statistics using Mac Nemar, Wilcoxon and Pearson’s Chi-square tests. Results: after the strategy, the proportion of parents and caregivers who identified the first permanent molar and its importance increased (38.7% vs 67.6%), the frequency of non-cavitational caries in PMP decreased (45.7% vs 26.5%), an increase was observed in the reported use of dental floss (40% vs 67.6%) and dental consultation of school children (74.3% vs 97.1%), as well as a significant improvement in the quality of brushing (Me % placa = 85% vs 30%). Conclusion: the effectiveness of the educational intervention was demonstrated with regard to knowledge about PMP and oral hygiene practices, as protective factors for its permanence in the mouth.